2020
DOI: 10.3389/fonc.2020.00576
|View full text |Cite
|
Sign up to set email alerts
|

Transducin-Like Enhancer of Split-1 Inhibits Malignant Behaviors in vitro and Predicts a Better Prognosis in Pancreatic Ductal Adenocarcinoma

Abstract: Background: Transducin-like enhancer of split-1 (TLE1), a member of the Groucho/TLE family of transcriptional corepressors, has been reported to be involved in the tumorigenesis of various cancers and function as a clinical prognostic indicator. However, the mechanisms and prognostic significance of TLE1 in pancreatic ductal adenocarcinoma (PDAC) have not been elucidated. Methods: In this study, western blot analyses and real-time polymerase chain reaction (RT-PCR) were employed to evaluate the expression of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The prognostic value of TLE1 expression was evaluated in other types of cancer. Wang et al, (2020) showed that high TLE1 expression was significantly associated with better disease-specific survival (DSS), in patients with Pancreatic Ductal Adenocarcinoma. Also, Lee et al, (2016) showed that TLE1 expression is a good indicator of prognosis in patients with gastric cancer both OS and DFS.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of TLE1 expression was evaluated in other types of cancer. Wang et al, (2020) showed that high TLE1 expression was significantly associated with better disease-specific survival (DSS), in patients with Pancreatic Ductal Adenocarcinoma. Also, Lee et al, (2016) showed that TLE1 expression is a good indicator of prognosis in patients with gastric cancer both OS and DFS.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation ability of DU-145 and LNCap cells was assessed by CCK-8 assay (Dojindo) [ 22 ]. The transfected cells (5 × 10 3 cells/well) were seeded in a 96-well cell culture plate and cultured at 37°C.…”
Section: Methodsmentioning
confidence: 99%